Menjadi Relevan: Peran Serta Perguruan Tinggi untuk Menyediakan Pembelajaran Kontekstual Bagi Pelajar - Elisabeth Dewi (Sapientia Humana: Jurnal Sosial Humaniora, 2021)
Education is viewed as being distant from the reality of students’ life. Through contextual learning, students suppose to understand social reality and to have skills also knowledge to prepare their lives after graduated. However, this contextual learning method is often not a priority for schools and teachers due to limitation in meeting curriculum standards as well as limited expertise of teachers to provide education that is in accordance with the lives and realities of their students. To fill the gap in the provision of contextual education, it is necessary to take an active role from various groups, such as universities through community service activities (pengabdian masyarakat) to complement primary and secondary schools teaching by introducing knowledge and skills connected to student’s experiences and social realities. Community service activities carried out by Department of International Relations and Informatics Engineering, Parahyangan Catholic University at Bani Yasin Sukabumi Islamic boarding school (pesantren) that aim to assist the pesantren with contextual knowledge and experience relevant to their students’ day to day environment. On the one hand, this activity provides students with local content such as agriculture for youth, migrant workers issues and process, basic literacy knowledge, and values ​​in the affective domain. Students can also connect their daily lives experiences with the introduced knowledge and skills in a pleasant atmosphere. This activity further encourages the importance of participation and collaboration for effective contextual learning process. On the other hand, this community service activity is constrained by the pandemic situation which hinders the process of reflection and optimization of students’ creativity to process the knowledge gained from this interaction into how they solve their daily life problems.